Al-Qalb wa ʼAlāqatuh bi al-Maʼrifah al-Ṣūfiyyah - Irfan Mas'ud (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2006)
In Islamic mysticism (tasawuf) literature, gnostic (makrifah) term is on the important position. It can be said that there is no sufi that did not discuss this term, whether the discussion is done systematically or as an expression of their spiritual experience. In this paper explained the perspective of Syekh Yusuf al-Makassari, a sufi who lived in M, makrifah, and its relation to Tauhid and Zikir.